Screening for resistance against bruchid (Callasobruchus maculatus) damage in blackgram - M, Indhu S; N, Manivannan; A, Mahalingam; Kavitha, Zadda; J, Souframanien (The Indian Journal of Agricultural Sciences, 2020)
Bruchid (Callasobruchus sp.) is the most devastating pest causing severe damage to the blackgram seeds during storage. Hence it is essential to identify a genotype which is resistant to bruchids. A total of 61 blackgram genotypes were artificially screened for their resistance against Callasobruchus maculates at National Pulses Research Center, Tamil Nadu Agricultural University, Pudukkottai during 2017. Among the genotypes TU 68 had comparatively less number of adult emergence in 40, 50, 60, 70, 105 days after infestation, less seed damage (%) and less seed weight loss (%). Genotype TU 68 was found to be resistant in the confirmatory experiment also. Less number of adult emergences even at the end of 105 days indicated the prolonged developmental period which is also a mechanism of bruchid resistance. TU 68 was derived from the interspecific cross TU 94-2 × Vigna mungo var. silvestris. TU 68 could be utilized in the hybridization programme to develop high yielding blackgram variety inbuilt bruchid resistance.